2018
DOI: 10.1177/0733464818807468
|View full text |Cite
|
Sign up to set email alerts
|

Older Adult Internet Use and eHealth Literacy

Abstract: We examine Internet use and eHealth literacy among older adults (aged 55+ years) who were patients at clinics serving low-income populations. Participants included 200 minority and White adults who completed interviews based on a technology acceptance conceptual model. A total of 106 participants (53.0%) used the Internet; utilization was associated with personal characteristics (age, ethnicity, education, poverty), computer characteristics (number of e-devices, computer stress), social support (marital status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
180
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(215 citation statements)
references
References 39 publications
(50 reference statements)
13
180
2
Order By: Relevance
“…The necessity of long-term business modelling to ensure sustainable implementation of eHealth interventions is in line with previous research, both for dementia47 and other populations 48 . In this regard, mapping the surrounding health care context and other financial stakeholders in relation to the intervention characteristics is essential, for instance by applying the Business Model Canvas 49 .…”
Section: Mapping the Implementation Context And Identifying Potentialsupporting
confidence: 77%
See 3 more Smart Citations
“…The necessity of long-term business modelling to ensure sustainable implementation of eHealth interventions is in line with previous research, both for dementia47 and other populations 48 . In this regard, mapping the surrounding health care context and other financial stakeholders in relation to the intervention characteristics is essential, for instance by applying the Business Model Canvas 49 .…”
Section: Mapping the Implementation Context And Identifying Potentialsupporting
confidence: 77%
“…The BMC maps a product or service's value proposition, key activities, key resources, key partners, cost structure, customers relationships, distribution channels, and revenue. The BMC has previously been used to map business models for eHealth [45][46][47][48] . Applying the BMC to eHealth interventions for caregivers of people with dementia that are already being used in practice, enables the investigation of factors relating to the sustainable success of these interventions and their potential market.…”
Section: Ehealth Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the sample was diverse in age and included a broad range of educational levels which can reflect internet usage and access. In addition to age being a factor in internet usage, previous research in older adults has shown that those with higher educational levels are more likely to use the internet [48,49]. Therefore, it is possible that as 'internet savvy' generations age, age will become less of a factor influencing internet usage and education and language will remain a major factor influencing internet usage compared with age.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%